2005
DOI: 10.1097/01.brs.0000157424.72598.ec
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic Study of MRI and Low Back Pain in 13-Year-Old Children

Abstract: In children, degenerative disc findings are relatively common, and some are associated with LBP. There appears to be a gender difference. Disc protrusions, endplate changes, and anterolisthesis in the lumbar spine were strongly associated with seeking care for LBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
114
4
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 37 publications
7
114
4
5
Order By: Relevance
“…9 They also found 10 disks from subjects who died after the first 2 decades in which the radial tears were seen in the absence of nuclear clefts. We found a higher prevalence of annular tears than nuclear degeneration in our study, which contrasts with the observations of Kjaer et al 12 The prevalence of signal-intensity loss reported by them was higher relative to that of annular tears. They reported almost 21.2% disks with abnormal signal intensity (defined as intermediate or hypointense signal intensity) but only 7.3% disks with annular tears (including 5.0% of disks with "high-intensity zones").…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…9 They also found 10 disks from subjects who died after the first 2 decades in which the radial tears were seen in the absence of nuclear clefts. We found a higher prevalence of annular tears than nuclear degeneration in our study, which contrasts with the observations of Kjaer et al 12 The prevalence of signal-intensity loss reported by them was higher relative to that of annular tears. They reported almost 21.2% disks with abnormal signal intensity (defined as intermediate or hypointense signal intensity) but only 7.3% disks with annular tears (including 5.0% of disks with "high-intensity zones").…”
Section: Discussioncontrasting
confidence: 57%
“…5 These results are, however, discordant with the observations of some prior investigators. 9,12 Haefeli et al 9 found that radial tears were relatively rare in first 2 decades of life, and nuclear clefts preceded radial and concentric tears. 9 There are a number of factors that may explain these differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 58 study samples that reported the prevalence of VESC in individuals, 45 were from clinical populations, two from the general population [81,82], four from the working population (including top athletes) [13,17,36,88], and the seven study samples of the non-LBP populations were from six studies [24,31,38,62,78,153]. The median prevalence of VESC was 6% in study samples of individuals without LBP (n = 7), 12% in the general population (n = 2), 6% in the working population (n = 4), and 43% in study samples from the clinical population (n = 45).…”
Section: Study Samplementioning
confidence: 99%
“…The prevalence of VESC varies greatly between the studies ranging from less than 1% [82] in adolescents from the Danish general population to 100% [41,149] in selected patient populations. A large number of studies and narrative reviews have reported on VESC in patient populations with specific LBP (e.g.…”
Section: Introductionmentioning
confidence: 99%